Overweight and underweight implements' impact on critical factors of rotational shot-putting technique - Klein, L. N.; Becker, J.; Whitten, J.; Peach, M. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
The purpose of this study was to evaluate the impacts of heavy and light implements on the kinematics of the rotational shot put technique. Ten collegiate shot putters completed three rotational shot put attempts using competition, overweight and underweight implements. Whole body kinematics were recorded on each throw to evaluate key aspects of shot putting technique including pelvis-torso separation, rear leg hip flexion, rear leg knee flexion, and peak pelvis angular velocity during specific phases of the throw. Results of this study highlight that when using an overweight implement, athletes have significantly less hip flexion compared to the competition-weighted implement (52.11° ± 15.47° vs. 31.98° ± 10.62°, p=.0097). No other critical factors of technique showed any significant changes between conditions. These findings support the strategic incorporation of heavy and light implements in rotational shot put training.